2014
DOI: 10.1093/nar/gku086
|View full text |Cite
|
Sign up to set email alerts
|

Hunting complex differential gene interaction patterns across molecular contexts

Abstract: Heterogeneity in genetic networks across different signaling molecular contexts can suggest molecular regulatory mechanisms. Here we describe a comparative chi-square analysis (CPχ2) method, considerably more flexible and effective than other alternatives, to screen large gene expression data sets for conserved and differential interactions. CPχ2 decomposes interactions across conditions to assess homogeneity and heterogeneity. Theoretically, we prove an asymptotic chi-square null distribution for the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…We did not find enrichment of the proposed consensus TIEG motif 5′GGTGTG3′ , which suggests that Cbt binds to degenerated or alternative motifs or may function through its interaction with other TFs. A recent study identified a novel Mad‐like motif in promoters of Cbt‐regulated genes . However, this new motif does not coincide with previously reported Cbt binding data .…”
Section: Resultscontrasting
confidence: 66%
“…We did not find enrichment of the proposed consensus TIEG motif 5′GGTGTG3′ , which suggests that Cbt binds to degenerated or alternative motifs or may function through its interaction with other TFs. A recent study identified a novel Mad‐like motif in promoters of Cbt‐regulated genes . However, this new motif does not coincide with previously reported Cbt binding data .…”
Section: Resultscontrasting
confidence: 66%
“…We first give an overview of the ChiNet method, which decides whether a subnetwork is conserved, or rewired in either topology or interaction strength across two conditions. In the comparative chi-square framework CPχ 2 first introduced in ( 41 ), rewired interactions were characterized by a heterogeneity chi-square. CPχ 2 can detect single strongly rewired interactions, but was not designed to detect subnetwork rewiring.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous CPχ 2 work on single interaction comparative chi-square analysis ( 41 ) established interaction heterogeneity \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\chi ^2_d(i)$\end{document} for each node in a network as follows: \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} \chi ^2_d(i) = \chi ^2_t(i) - \chi ^2_c(i) \quad (\text{Interaction heterogeneity}) \end{equation*}\end{document} which measures how far the interactions deviate from the pooled version. We proved that \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\chi ^2_d(i)$\end{document} asymptotically follows a chi-square distribution with v d ( i ) = v t ( i )- v c ( i ) d.f.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations